Functional and Quantitative MRI Mapping of Somatomotor Representations of Human Supralaryngeal Vocal Tract. (9th January 2017) - Carey, Daniel; Krishnan, Saloni; Callaghan, Martina F.; Sereno, Martin I.; Dick, Frederic
Abstract: Speech articulation requires precise control of and coordination between the effectors of the vocal tract (e.g., lips, tongue, soft palate, and larynx). However, it is unclear how the cortex represents movements of and contact between these effectors during speech, or how these cortical responses relate to inter-regional anatomical borders. Here, we used phase-encoded fMRI to map somatomotor representations of speech articulations. Phonetically trained participants produced speech phones, progressing from front (bilabial) to back (glottal) place of articulation. Maps of cortical myelin proxies (R1 = 1/T1 ) further allowed us to situate functional maps with respect to anatomical borders of motor and somatosensory regions. Across participants, we found a consistent topological map of place of articulation, spanning the central sulcus and primary motor and somatosensory areas, that moved from lateral to inferior as place of articulation progressed from front to back. Phones produced at velar and glottal places of articulation activated the inferior aspect of the central sulcus, but with considerable across-subject variability. R1 maps for a subset of participants revealed that articulator maps extended posteriorly into secondary somatosensory regions. These results show consistent topological organization of cortical representations of the vocal apparatus in the context of speech behavior.